Microfinance, Microcredit, and Women’s Empowerment: An Exploration of the Grameen Bank Experience for Social Inclusion - Del Sarto, Nicola; Bocchialini, Elisa; Gai, Lorenzo; Ielasi, Federica (Journal of Accounting and Finance, 2023)
Microfinance, originating in the mid-1800s but gaining modern prominence with Muhammad Yunus's Grameen Bank in 1970, has emerged as a potent tool for poverty alleviation. This paper explores the profound impact of microcredit on marginalized communities globally, particularly the empowerment of women, who constitute a majority of borrowers. Microcredit not only provides financial opportunities but also fosters confidence and belief in women's potential, transcending religious and national boundaries. Examining the origins and operations of microfinance, notably Grameen Bank, the paper distinguishes microfinance institutions from traditional banks. It addresses concerns about interest rates and presents compelling evidence linking microfinance access to poverty reduction. The core contribution of this research lies in its exploration of microcredit's dual function as an instrument for socioeconomic development and a catalyst for women's empowerment. We provide insights into how microcredit can contribute to fostering a more equitable world characterized by reduced poverty.